Penerapan Data Mining Untuk Menentukan Strategi Penjualan Pada Toko Raja Komputer Menggunakan Metode Clustering - Ayu Sri Wahyuni; Joy Nashar Utamajaya (JURIKOM (Jurnal Riset Komputer), 2022)
Toko Raja Computer Balikpapan is one of the laptop sales shops engaged in electronics with main products such as laptops, PC computers, and other accessories. Where the company every day must meet the needs of consumers and sales to be able to make the right decisions in determining the strategy. To be able to do this, Toko Raja Computer requires sales strategies to be able to attract buyers and increase company profits or revenues. In this study, data mining analysis was carried out by clustering techniques using the K-Means method. From the results of the research conducted, the results obtained from 1044 datasets of the Raja Computer sales list in 2021. So the results of clustering on the sales transaction data were 4 clusters of which there were 398 data following cluster 0, 363 data following cluster 1, 145 data following cluster 2 , and 138 data follow cluster 3, which means that clusters 0 and 1 are defined as products that must pay attention to the supply with the highest number, while clusters 2 and 3 are products with stock supply below clusters 0 and 1.